2007
DOI: 10.1080/14647270600973035
|View full text |Cite
|
Sign up to set email alerts
|

Confidence in the use of donor insemination: an evaluation of the impact of participating in a group preparation programme

Abstract: This paper argues that infertility can result in a range of negative emotional reactions, including a lack of confidence. This is more marked when donor insemination (DI) is used because of the additional shame this is associated with. Parents who do not feel confident may be less likely to share information about their use of DI with others and their child. Legislation in several countries has been introduced to abolish donor anonymity, but this has does not necessarily have an impact on parental confidence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
2
13
0
1
Order By: Relevance
“…Results of a recent study of a group counseling program for donor procedures indicated that its 60 participants had markedly increased confidence as a result of attending an educational seminar (27). This increased confidence impacted positively on their intention to share information about donor conception with future children.…”
Section: Importance Of Psycho-educational Consultationsmentioning
confidence: 93%
“…Results of a recent study of a group counseling program for donor procedures indicated that its 60 participants had markedly increased confidence as a result of attending an educational seminar (27). This increased confidence impacted positively on their intention to share information about donor conception with future children.…”
Section: Importance Of Psycho-educational Consultationsmentioning
confidence: 93%
“…Firstly, the experienced shortage of information, the lack of a consumer group for support, the lack of research on TPR families with an anonymous donor can enhance feelings of insecurity (and stigma) [37,38], making it harder to cope with these challenges and instigate the search for support with close family, friends. Secondly, the practice of a limited number of mandatory sessions prior to starting a TPR program might contain the risk that couples experience staff approval as a confirmation of having worked through the process of TPR rather than encouraging an ongoing process.…”
Section: Discussionmentioning
confidence: 99%
“…Couples (especially lesbian couples) were more likely to respond than SW, with many couples ' responses (86%) completed by both partners. Workshops built on German seminars with HCs considering DI (Thorn & Daniels, 2003;Daniels et al, 2007) to include lesbian couples, SW and those considering egg, embryo or double donation. An earlier paper reported the impact on treatment decision-making and on confi dence/comfort levels with disclosure (Crawshaw & Montuschi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Their intention was to tackle assumed adverse infl uences of shame and lowered confi dence. Outcomes included improved confi dence in the use of DI and intentions to be open, lowered partner differences and positive views about sharing experiences with peers (Thorn & Daniels, 2003;Daniels et al, 2007). No similar interventions have been identifi ed elsewhere although the need for greater attention to donor conception parenthood preparation was recently identifi ed (Nuffi eld Council on Bioethics, 2013).…”
Section: Introductionmentioning
confidence: 96%